Fiqh Tolerance in a Contemporary Context: The Response of State Islamic Religious University Students to Religious Extremism - Supardi Mursalin; Hamdan; Robeet Thadi; Mohamad Salik; M. Fijar Ishlahul Ummah (MILRev: Metro Islamic Law Review, 2024)
This study examines the application of fiqh tolerance in State Islamic Higher Education Institutions (PTKIN) within the context of contemporary challenges. The research focuses on student responses to religious extremism in Indonesia, which has become increasingly relevant in the era of digital media and globalization. This field study uses data collection methods, including interviews and documentation. Three key findings emerged from this study. First, most students firmly reject religious extremism, although a minority still supports it due to misinformation and the influence of narratives spread through digital media. Second, extremist recruitment strategies in PTKIN are carried out through religious activities, social media, and the dissemination of extremist ideologies through various channels, such as books, journals, and financial support, which have become more sophisticated using information technology. Third, preventive measures involve strengthening academic and non-academic understanding, including integrating religious moderation values into the curriculum, conducting seminars and training, and empowering student organizations to build resilience against extremism within the PTKIN environment. The academic contribution of this study lies in aligning fiqh tolerance with contemporary challenges, particularly in dealing with digital-based extremism, which has become more complex. This research offers a new perspective by integrating religious and social approaches to raise collective awareness among students at PTKIN. Furthermore, the findings enrich academic discourse by providing concrete recommendations for strengthening curricula based on religious moderation and developing adaptive preventive strategies in response to social and technological changes. This makes the study theoretically and practically relevant in creating a more inclusive and resilient higher education environment.